On measuring the contribution from firm turnover to aggregate productivity growth. Selection on profitability and not productivity - Thomas von Brasch (Statistics Norway, Research Department, 2015)
Foster et al. (2001) outline a framework that is commonly used to identify the contribution from firm turnover to aggregate productivity growth. The framework is not derived from economic theory and it implies that productivity levels determine the contribution from reallocation and firm turnover. In this paper, I outline an index for aggregate productivity growth based on economic theory. In contrast to common beliefs, I show that the contribution from firm turnover to aggregate productivity growth should be based on the profitability, and not the productivity, of these firms.
Keywords: D24; J24; L25; O47; C43; 330; Productivity; Profitability; Aggregation